PENGARUH KERAGAMAN PRODUK DAN ENDORSER TERHADAP KEPUASAN KONSUMEN PADA CAFE D’POTO SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Kholifah, Unniatul; Kusnadi, Edy; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is the activity, set of institutions, and steps involved in creating, informing, communicating, and exchanging offerings that have value for consumers. That way creating, informing, communicating is the right marketing strategy that can increase the development of Cafe D'poto in Situbondo. The purpose of this study was to analyze and test the effect of product diversity and endorser on consumer satisfaction at Cafe D'poto Situbondo with purchase intention as an Intervening Variable. The population of this research is all consumers of Cafe D'poto, Sumberkolak Village, Panarukan District, Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that product diversity has a significant positive effect on purchase intention, endorser has a positive significant effect on purchase intention, product diversity has a positive but not significant effect on consumer satisfaction, endorser has a positive but not significant effect on satisfaction consumers, purchase intention has a significant positive effect on consumer satisfaction, product diversity on consumer satisfaction through purchase intention has a significant positive effect, endorsers on consumer satisfaction through purchase intention have a significant positive effect.